Analisis Narasi Keislaman Moderat dan Dakwah Kultural dalam Podcast “LOGIN” Bersama Habib Husein Ja’far - Nur Atifa Oktavirani; Laila Fathul Muzahidah; Adhi Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
Podcast “LOGIN” with Habib Husein Ja’far as a form of contextual and transformative digital da’wah. Moderate Islam or wasathiyah is understood as a balanced, fair, and tolerant approach to diversity, and is relevant to the challenges of the times. In this context, podcasts become a new medium that allows da’wah to be carried out in a dialogical, reflective manner, and touches the emotional aspects of the audience, especially the younger generation. Habib Husein combines Islamic values ​​with a cultural approach through humor, modern analogies, and inclusive and humanist pop language. This strategy shows that da’wah is not just about conveying dogma, but also building understanding that is constructive and relevant to everyday life. Norman Fairclough’s critical discourse analysis is used to see how the production and consumption of discourse in this podcast represents participatory, creative, and responsive religious practices to social dynamics. Da’wah through podcasts is not only a means of conveying messages, but also a forum for interaction, contestation, and reinterpretation of religious meaning in the digital era.